MENENTUKAN LUAS OBJEK CITRA DENGAN TEKNIK SEGMENTASI BERDASARKAN WARNA PADA RUANG WARNA HSV: Determining the Image Object Area Using Color-Based Segmentation Technique in HSV Color Space - Oni, Muhammad; Kanata, Bulkis; Ratnasari, Dwi (DIELEKTRIKA, 2021)
The color image segmentation technique is one of many approaches used to extract information from an image. In this study, the calculation of the image object area was carried out using the color image segmentation technique in HSV color space. There are three objects that the area has calculated those are triangle, square, and circle. The object area calculated by multiply the image background original area with the proportion difference between the total number of object pixels and the sum of background pixels. The threshold value for the HSV filter was determined using two different approaches, which are the trial-and-error method and the multi-otsu thresholding method. The result of this study shows that the object area calculation system works pretty well. Using the trial-and-error method, the difference percentage mean of all objects is 1,35%, meanwhile, using the multi-otsu thresholding method is 1,31%. Keywords: Color segmentation, hsv, multi-otsu, object area.